Antibody and blood leukocyte response in Rhipicephalus sanguineus (Latreille, 1806) tick-infested dogs and guinea pigs - Szabo, MPJ; Aoki, V. L.; Sanches, FPS; Aquino, LPTCT; Garcia, M. V.; Machado, R. Z.; Bechara, G. H. (Elsevier B.V., 2003)
The dog is considered to be the natural host of Rhipicephalus sanguineus and is unable to develop appreciable resistance even after repeated feedings. The guinea pig develops strong resistance after one infestation with adult ticks. Antibody (IgG) titres against tick salivary gland antigens (SGAs) and blood leukocyte numbers in dogs and guinea pigs undergoing experimental R. sanguineus tick infestations were measured to detect a possible correlation with susceptibility or resistance of hosts. Since infested dogs develop an immediate hypersensitivity reaction to R. sanguineus antigens, total and anti-R. sanguineus SGA IgE levels were also measured in this host species. IgG and IgE antibody levels were determined by an enzyme-linked immunosorbent assay (ELISA) along three consecutive infestations of both hosts. Most dogs and guinea pigs displayed low IgG levels against R. sanguineus SGAs, though marked differences in individual response were observed. Although dog's total serum IgE levels increased significantly after infestations, no change in the amount of anti-salivary gland IgE was detected. Total and differential blood cell counts were determined in dogs and guinea pigs during primary and secondary infestation. In dogs, a tertiary infestation and a subsequent higher infestation level were also evaluated. Infested dogs did not display any alteration in blood leukocyte counts throughout the experiment. Guinea pigs, on the other hand, developed a significant basophilia during primary infestation which increased further during secondary infestation. These data reveal similarities and differences in the reactions of resistant and non-resistant hosts to ticks. They contribute for the understanding of such host-parasite relationships and will hopefully aid in the development of immune control of ticks. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: Rhipicephalus sanguineus; Ixodidae; Hematology; antibody; dog; Guinea pig